(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The visualization of the informational dimension linked to the urban environment organizes a perception articulated through an ecosystem of screens from which the hypermediated city emerges. This article examines the impact of different artistic productions that, as metaphors of physical-digital reality, configure the phenomenology of the landscape disposed by the technological imperative.